Cyclic β-glucans at the bacteria–host cells interphase: One sugar ring to rule them all - Guidolin, Leticia Soledad (2018)
Cyclic β‐1,2‐D‐glucans (CβG) are natural bionanopolymers present in the periplasmic space of many Proteobacteria. These molecules are sugar rings made of 17 to 25 D‐glucose units linked exclusively by β‐1,2‐glycosidic bonds. CβG are important for environmental sensing and osmoadaptation in bacteria, but most importantly, they play key roles in complex host–cell interactions such as symbiosis, pathogenesis, and immunomodulation. In the last years, the identification and characterisation of the enzymes involved in the synthesis of CβG allowed to know in detail the steps necessary for the formation of these sugar rings. Due to its peculiar structure, CβG can complex large hydrophobic molecules, a feature possibly related to its function in the interaction with the host. The capabilities of the CβG to function as molecular boxes and to solubilise hydrophobic compounds are attractive for application in the development of drugs, in food industry, nanotechnology, and chemistry. More importantly, its excellent immunomodulatory properties led to the proposal of CβG as a new class of adjuvants for vaccine development.